SIKAP MASYARAKAT TERHADAP HUTAN MANGROVE DI DUSUN PARIT PANGERAN DESA TANJUNG SALEH KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Simanjuntak, Damaris Rose; Fahrizal, M; Farahdiba, . (Universitas Tanjungpura, 2017)
The mangrove forest is a community plant or an individual plant species that form a community of mangrove ecosystem in coastal area. This ecosystem has unique characteristics, distinctive and has the potential of biological richness. Coastal marine ecosystem is a natural resource that is productive as a provider of energy for community life in it. Tanjung Saleh village in Sungai Kakap district Kubu Raya regency has a mangrove forest which cover around 5000 hectare. The community in Tanjung Saleh village especially in Sub village Parit Pangeran has utilized the mangrove forest resources to fulfill their daily needs. The vegetation consist of Avicenia sp, Bakau (Rhizophora sp), Berembang, Coconut, Umbal wood, and Nipah (Nypa fructicans). The research aimed to determine the perception and attitude of community in Parit Pangeran sub village towards mangrove forest and to evaluate the relationship between knowledge, cosmopolitan, perception and attitude on mangrove forest of community in Parit Pangeran sub village. Data was collected with in-depth interview to the people in Parit Pangeran sub village with total responden was 120 people. The result showed that 52 responden (43.33%) has a positive perception on mangrove forest, meanwhile 47 responden (39.17%) was neutral and 21 responden (17.5%) has a negative perception. There are a relationship between level of knowledge and attitude of the community on mangrove forest. People with high knowledge on the importance function of mangrove forest have a tendency to have positive attitude and vice versa. Mangrove forest need to conserve and the community of Parit Pangeran sub-village still need to increase their knowledge on how to manage the mangrove forest in their area. Keywords: Attitude, Kubu Raya regency, mangrove forest, perception, Parit Pangeran sub-village.